Comparison and oscillation results for delay difference equations with oscillating coefficients - Weiping Yan; Jurang Yan (International Journal of Mathematics and Mathematical Sciences)
In this paper we consider the oscillation of the delay difference equation with oscillating coefficientsxn+1−xn+∑i=1npi(n)xn−ki(n)=0,   n≥0.Some comparison and oscillation results are obtained.